New and young firms: Entrepreneurship policy and the role of government – evidence from the Federation of Small Businesses survey - David Pickernell (Journal of Small Business and Enterprise Development, 2013)
The purpose of this paper is to investigate whether new and young firms are different from older firms. This analysis is undertaken to explore general characteristics, use of external resources and growth orientation. Data from the 2008 UK Federation of Small Businesses survey provided 8,000 responses. Quantitative analysis identified significantly different characteristics of firms from 0‐4, 4‐9, 9‐19 and 20+ years. Factor analysis was utilised to identify the advice sets, finance and public procurement customers of greatest interest, with ANOVA used to statistically compare firms in the identified age groups with different growth aspirations. The findings reveal key differences between new, young and older firms in terms of characteristics including business sector, owner/manager age, education/business experience, legal status, intellectual property and trading performance. New and young firms were more able to access beneficial resources in terms of finance and advice from several sources. New and young firms were also able to more easily access government and external finance, as well as government advice, but less able to access public procurement. New and young firms are utilising external networks to access several resources for development purposes, and this differs for older firms. This suggests that a more explicit age‐differentiated focus is required for government policies aimed at supporting firm growth. The study provides important baseline data for future quantitative and qualitative studies focused on the impact of firm age and government policy.